Linkage development as industrial policy: The state and structural transformation in resource-rich countries - Imaduddin Abdullah; Andrew Sumner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This paper examines Indonesia's upgrading within the global nickel value chain. Indonesia's transformation from a major nickel ore exporter into an integrated producer of refined nickel products offers important lessons for resource-rich developing countries seeking economic diversification. Drawing on evidence from Indonesia's strategic shift towards midstream and downstream manufacturing, this paper examines how policy choices and state intervention can reshape a country's position in global value chains. This paper shows the importance of linkage development in achieving upgrading in resource-based manufacturing. The Indonesian case demonstrates that it is possible for resource-rich countries to move up the value chain when appropriate policies are implemented. However, this industrial transformation also highlights critical challenges, including environmental concerns from coal-powered processing and the nuanced relationship between state direction and market forces. By analysing Indonesia's upgrading trajectory in nickel, this paper contributes insights to ongoing debates about industrialization pathways in resource-rich developing countries and the role of strategic state intervention in fostering industrial development.
Keywords: O14; O25; F63; 330; industrialization; structural transformation; industrial policy; Indonesia